A Spontaneous Coronary Artery Dissection Case Noticed during a Primary PCI - Ismail Dogu Kilic; Halil Tanriverdi; Harun Evrengul; Sukru Gur (Cardiology Research and Practice)
Spontaneous coronary dissections (SCAD) can be asymptomatic or can manifest itself as any of the clinical spectrum of the ischemic heart disease. In this report, we present a 65 year old man presented with myocardial infarction in whom coronary angiography a nonocclusive SCAD was noticed in addition to a very late stent thrombosis and make a brief overview of the treatment for SCAD.